Validation of sejahtera living inventory - Nordin, Mohamad Sahari; Hussein, Suhailah; Hashim, Khairusy Syakirin Has-Yun (IIUM Press, 2022)
The first aim of the study was to construct-validate the sejahtera living inventory in terms of its convergent validity, discriminant validity, and composite reliability. The second purpose was to evaluate sample type-invariant of the maqasid shariah driven measurement model, and therefore its generality. An online self-reported Sejahtera Living inventory was created to collect the data. It is a questionnaire that contains 21 content-validated items measuring five facets of sejahtera living, namely the preservation of religion, life, intellect, dignity, and wealth and resources. A total of 1,057 students and employees at a public university in Malaysia participated in the study. The results of confirmatory factor analysis found that the five-factor sejahtera living model was consistent with the data; the statistics satisfied the requirements deemed necessary for a good fit measure. The results also supported the prevalence of the model’s configural invariance and metric invariance. Thus, the study offers additional understanding about the adequacy of a measure of good life based on maqasid shariah.